Human Rights of Women - Aida González Martínez (Washington University Journal of Law & Policy, 2001)
Freedom, justice, and peace are based on the recognition of the dignity inherent to the human family and to its equal and inalienable rights. It is thus emphasized in the third paragraph of Article 1 of the United Nations Charter when referring to the endeavor of the international community to achieve international cooperation in “solving international problems of an economic, social, cultural or humanitarian character, and in promoting and encouraging respect for human rights and for fundamental freedoms for all without distinction as to race, sex, language, or religion.” It is also declared in the first paragraph of the preamble of the international covenants on civil and political rights and on economic, social, and cultural rights.
Keywords: Human rights; Women; United Nations; United Nations. Convention on the Elimination of All Forms of Discrimination Against Women